Development of project management documentation for enterprise resource planning system implementation / Mohd Shaharuddin Mohd Izzuddin - Mohd Izzuddin, Mohd Shaharuddin (2003)
Although project management stages and functions are very visible in publications of the professional societies, it has not been known to what extent the stages and functions have actually being utilized by project management practitioners from project startup till closedown. More importantly, how can a series of forms, templates, checklists and other related documents be developed in each project management stage and function. To fill the gap, this study presents a development and application of a series of forms, templates and checklists in each project lifecycle that will ensure the success of Baan Enterprise Resource Planning (ERP) system implementation project. All these documents are known as Project Management Documentation (PMDs). Some of the PMDs are not unique to Baan ERP implementation only. These PMDs have been applied in the Baan ERP implementation in two different types of industries in United Motor Work (UMW). The validity of the PMDs was also tested based on its usefulness and ease of use in both types of industries. The findings showed that by systematically utilizing the designed PMDs, one can improve his or her skills as an effective and efficient Project Manager (PM). Also, these PMDs will aid in keeping high value projects on time, within scope, within budget, with quality deliverables and increased customer satisfaction.